Phương pháp giảm bong nứt lớp màng niken trên bề mặt điện cực trơ titan trong quá trình điện phân - Thắng và cộng sự, Phạm Đức (Vietnam Journal of Chemistry, 2014)
The experiments producing nickel by the way of electrolyzing nickel sulfate were resulted. The researches had been conducted with the concentration of NiSO4.7H2O solution about 200 g/l, electric current density about 5 A/dm2 and electric potential about 5 V. The electrolyse of nickel sulfate had been gained some thin nickel plates on the surface of inert titanium cathodes. The results showed that the peeling & cracking places have a distribution of large amount of rough inclusions with grain sizes from 5 to 10 mm. In the edges of thin nickel plates there were high irregular electric current density, therefore the thickness of plate is also different leading to the difference of surface tension in thin plate margins and making crack of nickel plate margin. The use of  SLS-1 compound as follows H2SO4 + KC12H25.SO3 according to fixed proportion to permit dissolving almost all inclusions, the retained inclusion quantity was very small smooth only about 1 mm. The result had been gained whole thin nickel plates.